2013
DOI: 10.1021/nn4039589
|View full text |Cite
|
Sign up to set email alerts
|

Polymersome Shape Transformation at the Nanoscale

Abstract: Polymer vesicles, also named polymersomes, are valuable candidates for drug delivery and micro- or nanoreactor applications. As far as drug delivery is concerned, the shape of the carrier is believed to have a strong influence on the biodistribution and cell internalization. Polymersomes can be submitted to an osmotic imbalance when injected in physiological media leading to morphological changes. To understand these osmotic stress-induced variations in membrane properties and shapes, several nanovesicles made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
111
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(115 citation statements)
references
References 61 publications
4
111
0
Order By: Relevance
“…Bicontinuous cubic structures have been reported as well28. Another study showed polymersomes that deflate to form nested vesicles29, possibly through a sequence of intermediate vesicle shapes such as prolate spheroids, discs and stomatocytes30, which unfortunately were not observed. The studies above have been rather empirical in nature, despite the existence of detailed theoretical bending energy models, predicting the shape of phospholipid vesicles as a function of reduced volume and surface area difference31.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Bicontinuous cubic structures have been reported as well28. Another study showed polymersomes that deflate to form nested vesicles29, possibly through a sequence of intermediate vesicle shapes such as prolate spheroids, discs and stomatocytes30, which unfortunately were not observed. The studies above have been rather empirical in nature, despite the existence of detailed theoretical bending energy models, predicting the shape of phospholipid vesicles as a function of reduced volume and surface area difference31.…”
mentioning
confidence: 95%
“…The total amount of water in the solvent mixture is a crucial parameter, as it not only sets the osmotic pressure across the polymersome membrane, but, owing to the amorphous glassy nature of the PS block, it also (indirectly) modifies its flexibility and its permeability24. Because of the glassy nature of the PS part of the polymersome membrane combined with the fact that the PS part of the polymersome membrane is rather long (>133 repeating units), the timescales of the shape transformations are much longer (several hours25) compared with those observed in lipid vesicles or in polymersomes assembled from polymers with a glass transition temperature much lower than that of PS, which usually is in the order of seconds to minutes2932. This makes it possible to probe the whole shape change process carefully in time.…”
mentioning
confidence: 99%
“…12,13 In addition, the shape of these polymersomes can be transformed into a large array of morphologies. [14][15][16] In general, vesicles can change shape from an initially spherical morphology via two possible routes: deflation via oblates (discs) or deflation via prolates (rods) as is shown in Figure 1 In order to gain more information about the shape of the formed structures, dry and cryoelectron microscopy techniques, both in scanning (SEM) and transmission (TEM) mode, are the method of choice. 18 In some cases differentiation between different morphologies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…4). Physically, shape transformation can be accomplished through out-of-equilibrium processing of polymersomes that have complementary chemical features (such as rigidity and porosity) so that otherwise inaccessible forms can be accessed through careful control of conditions such as the composition of organic solvents, rate of addition of aqueous solution, temperature cycling, osmotic shock and chemical cross-linking [64,65]. In particular, nanotubes (tubular polymersomes) are exciting candidates for the development of NVs due to their high aspect ratio and potential for immunotherapy, alongside drug delivery.…”
Section: Morphological Engineering Of Polymeric Nanostructuresmentioning
confidence: 99%